2019
DOI: 10.1146/annurev-marine-010318-095300
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Coral Loss, and the Curious Case of the Parrotfish Paradigm: Why Don't Marine Protected Areas Improve Reef Resilience?

Abstract: Scientists have advocated for local interventions, such as creating marine protected areas and implementing fishery restrictions, as ways to mitigate local stressors to limit the effects of climate change on reef-building corals. However, in a literature review, we find little empirical support for the notion of managed resilience. We outline some reasons for why marine protected areas and the protection of herbivorous fish (especially parrotfish) have had little effect on coral resilience. One key explanation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(160 citation statements)
references
References 173 publications
(200 reference statements)
8
131
0
4
Order By: Relevance
“…The findings in this study reinforce the idea that coral reef conservation depends on a suite of management strategies, including both local and global strategies , Mcleod et al 2019. Although warming oceans constitute the primary threat to corals by causing bleaching events and disease outbreaks (Muller et al 2008, Weil and Rogers 2011, Hughes et al 2018, Bruno et al 2019), local environmental factors may interact with temperature to influence coral health. Depending on the nature of this interaction, local factors may provide new targets for ameliorating the impacts of warming oceans on octocorals, scleractinian corals, and other important reef invertebrates (Ban et al 2014, Côt e et al 2016).…”
Section: Conclusion and Management Implicationssupporting
confidence: 77%
“…The findings in this study reinforce the idea that coral reef conservation depends on a suite of management strategies, including both local and global strategies , Mcleod et al 2019. Although warming oceans constitute the primary threat to corals by causing bleaching events and disease outbreaks (Muller et al 2008, Weil and Rogers 2011, Hughes et al 2018, Bruno et al 2019), local environmental factors may interact with temperature to influence coral health. Depending on the nature of this interaction, local factors may provide new targets for ameliorating the impacts of warming oceans on octocorals, scleractinian corals, and other important reef invertebrates (Ban et al 2014, Côt e et al 2016).…”
Section: Conclusion and Management Implicationssupporting
confidence: 77%
“…While there are differing views on the effectiveness of managing parrotfish abundance to promote reef resilience in the western Atlantic region (Adam et al 2015;Bozec et al 2016;Steneck et al 2018;Bruno et al 2019), our results highlight the importance of balancing any ecological benefits of herbivore management against the potential cost of increased bioerosion. What is clear is that more direct measurements are badly needed to empirically improve our prediction of the erosional side of the carbonatebudget equation.…”
Section: Discussionmentioning
confidence: 75%
“…Protection of reefs requires effective management plans that can mitigate the negative impacts of local and global stressors and conserve ecosystem functioning. Much is known about the major threats to coral reefs, including climate change and overfishing (Graham et al 2015;Bruno et al 2019), and several key species living on coral reefs have been identified (Bellwood et al 2004;Alvarez-Filip et al 2009;Brandl et al 2019). However, there is much less clarity about what exactly a functioning coral reef is and how it is influenced by the hyperdiverse communities that make coral reefs one of the most remarkable ecosystems on the planet.…”
Section: Front Ecol Environmentioning
confidence: 99%